Case Report: Lung cancer with rare cardiac and other multiple metastases - Chen, Li; Zhang, Jing; Zhang, Chunquan (Frontiers in Cardiovascular Medicine, 2024)
Metastasis to the left atrium is exceptionally uncommon, occurring at a rate of only 3.1%. The clinical manifestations of lung cancer metastasizing to the heart can vary widely. They range from paraneoplastic syndrome, dyspnea, and ST-segment elevation on an electrocardiogram to no clinically significant symptoms. Diverging from typical metastatic patterns observed in lung cancer, this case report presents a detailed description, from the perspective of the microenvironment, of a rare instance where lung cancer metastasized to the mediastinal lymph nodes, adrenal glands, brain, and notably, the left atrium, in a non-smoking female patient.